Robust Stabilization for Nonlinear Differential Inclusion Systems Subject to Disturbances - CAI, Xiu-Shan (Zi dong hua xue bao, 2010)
The stabilization problem of nonlinear differential inclusion (NDI) systems with disturbances is dealt with in this paper. First, based on the convex hull Lyapunov function (CHLF) approach, a continuous state feedback law is designed, which can globally asymptotically stabilize this kind of systems without disturbances. Second, by the state feedback, the reachable set under two classes of bounded disturbances is achieved simultaneously. Finally, a numerical example is used to illustrate the effectiveness of the proposed design technique.